Methods and computational tools to study eukaryotic cell migration in vitro - Toscano, Elvira; Cimmino, Elena; Pennacchio, Fabrizio A.; Riccio, Patrizia; Poli, Alessandro; Liu, Yan-Jun; Maiuri, Paolo; Sepe, Leandra; Paolella, Giovanni (Frontiers in Cell and Developmental Biology, 2024)
Cellular movement is essential for many vital biological functions where it plays a pivotal role both at the single cell level, such as during division or differentiation, and at the macroscopic level within tissues, where coordinated migration is crucial for proper morphogenesis. It also has an impact on various pathological processes, one for all, cancer spreading. Cell migration is a complex phenomenon and diverse experimental methods have been developed aimed at dissecting and analysing its distinct facets independently. In parallel, corresponding analytical procedures and tools have been devised to gain deep insight and interpret experimental results. Here we review established experimental techniques designed to investigate specific aspects of cell migration and present a broad collection of historical as well as cuttingedge computational tools used in quantitative analysis of cell motion.